An enzyme-linked immunosorbent assay for hypoxia marker binding in tumours. - Raleigh, J. A. (Nature Publishing Group, 1994)
An enzyme-linked immunosorbent assay (ELISA) has been developed for measuring the in vivo binding of a hexafluorinated 2-nitroimidazole (CCI-103F) in tumour tissue biopsies. The binding of CCI-103F is believed to reflect the presence of hypoxia in tumours. The ELISA provides a sensitive and convenient method of measuring CCI-103F binding which does not require the injection of radioactive reagents. The ELISA is based on reagents prepared from synthetic antigens formed by the reductive activation and binding of CCI-103F to proteins in novel test tube experiments. Calibration of the ELISA involved comparing the ELISA with the radioactivity contained either in protein-CCI-103F adducts formed in vitro with tritiated CCI-103F or in tissues isolated from a tumour-bearing dog which had been injected with tritium-labelled CCI-103F. The two approaches to calibration are compared. The scope and limitation of the ELISA for measuring the binding of CCI-103F is discussed and an example of the application of the ELISA to measuring changes in tumour hypoxia in canine patients undergoing fractionated radiation therapy is presented. IMAGES: